Revisions to the Classification, Nomenclature, and Diversity of Eukaryotes - Adl, Sina M; Bass, David; Lane, Christopher E; Lukeš, Julius; Schoch, Conrad L; Smirnov, Alexey; Agatha, Sabine; Berney, Cedric; Brown, Matthew W; Burki, Fabien; Cárdenas, Paco; Čepička, Ivan; et al. (The Journal of eukaryotic microbiology, 2019)
This revision of the classification of eukaryotes follows that of Adl et al., 2012 [J. Euk. Microbiol. 59(5)] and retains an emphasis on protists. Changes since have improved the resolution of many nodes in phylogenetic analyses. For some clades even families are being clearly resolved. As we had predicted, environmental sampling in the intervening years has massively increased the genetic information at hand. Consequently, we have discovered novel clades, exciting new genera and uncovered a massive species level diversity beyond the morphological species descriptions. Several clades known from environmental samples only have now found their home. Sampling soils, deeper marine waters and the deep sea will continue to fill us with surprises. The main changes in this revision are the confirmation that eukaryotes form at least two domains, the loss of monophyly in the Excavata, robust support for the Haptista and Cryptista. We provide suggested primer sets for DNA sequences from environmental samples that are effective for each clade. We have provided a guide to trophic functional guilds in an appendix, to facilitate the interpretation of environmental samples, and a standardized taxonomic guide for East Asian users.
Keywords: terminologie jako téma; Terminology as Topic; taxonomy; Phylogeny; parasite; fungus; Algae; Eukaryota; protozoa; systematics; biodiverzita; fylogeneze; flagellate; amoebae; ecology; plankton; microbiology; biodiversity; ciliate; Biodiversity